CONCENTRATION OF WATER POLLUTION INDICATORS BACTERIA IN SIRIH PADANG SUMATERA BARAT - Ferdana, Gilang; Nursyirwani, Nursyirwani; Amin, Bintal (Asian Journal of Aquatic Sciences, 2021)
This research was conducted in October 2019 in the waters of Sirih Bay Padang, West Sumatra Province. The objective of this research aimed was to determine the number of bacterial cells as an indicator of water pollution (total coliform and Escherichia coli) in the waters of Sirih Bay, Padang. The method used in this study was a survey method. Polluted waters in Sirih Bay as sampling location was divided into 3 stations, namely the PLTU area (St. I), near BPBALP Padang (St. II) and a residential area (St. III). Isolation of total coliform and fecal coliform bacteria was carried out by assumption and affirmation tests which were further identified and carried out physiological and biochemical properties. The results showed the total number of coliforms in Sirih Bay waters in the assertion test using BGLB media ranged from 75-460 MPN/ml. This indicates the existence of pollution of coliform bacteria in these waters based on the Decree of the State Minister of Environment No. 51 of 2004 concerning Sea Water Quality Standards, the maximum level of total coliform bacteria is 1000 MPN / 100 ml. The results of this study indicated that the waters of Sirih Bay are considered to be in poor condition